Utilizing learner language to craft well–targeted endorsements in English language teaching practices - Nasrullah Nasrullah; Elsa Rosalina; Eka Puteri Elyani (Universitas Ahmad Dahlan, 2020)
Learning a foreign language for those who have their first and second language often puts learners in imperfection mastery such as irrelevant lexical choice, and source cultural bounds language utterances. Knowing the concepts merely cannot guarantee the process of avoiding mistakes or errors that learners have. There has been an amount of research on learner language which focuses on language corpus but little on highlighting the research specific language components grammatically contributing to language learners’ competence. Therefore, to fill the void, this study aimed at scrutinizing and yielding information on the practical way of phenomena in Indonesians’ interference by knowing the students’ feature descriptions of language competence. In this research, a guided interview was used to sub-ethnic of Banjarese which covered several Banjar Kuala and Banjar Hulu pre-service English teachers in getting the data of this study. The findings reveal language problems in lexical aspect, semantic confusion, incorrect use of word-formation pattern, prepositional misuse, and problems in language syntax and discourse. The implication of this study calls for recommendations to adopt techniques in mitigating suggested learner language in the area of subject-verb concord, tenses, and lexical problems in a process of language development